1975
DOI: 10.1007/bf00369097
|View full text |Cite
|
Sign up to set email alerts
|

Generation time, length of life, instar duration and frequency of moulting, and their relationship to temperature in eight species of cladocera from the River Thames, reading

Abstract: Data on generation time, length of life, instar duration and frequency of moulting at a range of constant temperatures are given for eight species of epiphytic Cladocera from the River Thames. For each species each of the above events was inversely related to temperature. The number of juvenile instars was constant for a particular species, but varied between species; large species tending to have more juvenile instars than small species. A similar size relationship was found for generation time. Juveniles mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 17 publications
6
59
0
1
Order By: Relevance
“…Embryonic development in some crustaceans is highly dependent on water temperature (Bottrell, 1975;Herzig, 1983). In the present study, the crayfish P. acanthophorus embryos developed at an average temperature of 23.8 ± 2.2 °C during January-March.…”
Section: In C Destructor and García-guerrero Et Al (2003) In C Qumentioning
confidence: 59%
“…Embryonic development in some crustaceans is highly dependent on water temperature (Bottrell, 1975;Herzig, 1983). In the present study, the crayfish P. acanthophorus embryos developed at an average temperature of 23.8 ± 2.2 °C during January-March.…”
Section: In C Destructor and García-guerrero Et Al (2003) In C Qumentioning
confidence: 59%
“…Considering that moulting is not synchronised in the population, an increasing chitin level in our samples reflects an increase of the proportion of animals that are in a moulting stage. As the moulting frequency is closely related to temperature (Bottrell 1975), this may explain why a positive correlation was found between chitin level in Daphnia magna and temperature.…”
Section: Discussionmentioning
confidence: 97%
“…It is well-known that the duration of the embryonic development in the Cladocera depends strongly on the temperature (Bottrell, 1975a(Bottrell, , 1975b. For example, Bottrell observed an embryonic development of 76 h for A. harpae under 20°C, while Melão (1999) found that the development is about twice as fast (37 h) for the same species -though for a population from a different regionunder 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…An approximate sequence of embryonic stages was superficially described only for a single chydorid species, Leydigia acanthocercoides (Leydig, 1860) (Murugan and Job, 1982) and for the closest relative of (Kotov, 1996) Bottrell (1975aBottrell ( , 1975b, Melão (1997Melão ( , 1999 and their own observations. From our data, we can say that the general patterns of the sequence of events in chydorid embryogenesis is similar to that in other anomopods, such as the daphniids Daphnia magna (Obreshkove and Frazer, 1940), D. hyalina and D. galeata (Kotov and Boikova, 2001), and Ceriodaphnia reticulata (Shuba and De Costa, 1972).…”
Section: Discussionmentioning
confidence: 99%